Effects of COVID-19 Lockdown on Time in Therapeutic Range (TTR) for Warfarin Users - Aktaş, İbrahim and Sarıoğlu, Güney and Yaşar, Erdoğan (The European Research Journal, 2026)
Objective: This study investigated the impact of COVID-19 lockdown measures on Time in Therapeutic Range (TTR) for patients receiving warfarin therapy. Methods: A retrospective cohort study was conducted at a tertiary care hospital in Malatya. Patients receiving warfarin for at least one year before and after March 11th, 2020 (the start of pandemic) were included (n=112). Demographic data, comorbidities, medications, and International Normalized Ratio (INR) results were collected. TTR was calculated using the Rosendaal method. Results: The mean TTR before the pandemic was 56.91%, significantly higher than the 40.23% observed during the pandemic (P<0.001). INR measurement intervals also increased significantly during the pandemic (34.2 days pre-pandemic vs. 50.9 days during the pandemic, P<0.001). This effect was most pronounced in patients over 65 years old (P<0.001). Conclusion: COVID-19 lockdown measures significantly decreased TTR and extended INR monitoring intervals for warfarin users. These findings were particularly concerning in the elderly population. Strategies to ensure optimal warfarin monitoring during pandemics or disasters are crucial to prevent complications.